Hematopoietic stem cell transplantation for neuroblastoma - Breviglieri, Carla Nolasco Monteiro; Michalowski , Mariana Bohns; Gregianin, Lauro; Castro Júnior, Claudio Galvão (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
The indications for hematopoietic stem cell transplantation in solid tumors in children do not change a lot since our first Brazilian consensus publication in 2009. In this article, we are going to review indications to hematopoietic stem cell transplantation for neuroblastoma. For the consensus, a review was made using the most relevant articles, and a series of meetings was done to discuss the recommendations.